Tindak Ilokusi Ekspresif Dalam Komik Big Bad Wolf: The Baddest Day dan Terjemahannya - Gilang Fadhilia Arvianti (TRANSFORMATIKA, 2016)
This article focuses on analyzing of expressive illocutionary act in the Big Bad Wolf: The Baddest Day comic and its translation Serigala Jahat: Hari Terburuk. Besides, classifying the type of expressive illocutionary actin the comic, it is also studied the techniques used by translator in translating expressive illocutionary act from source text to the target text. By using techniques used by translator, it could be seen the quality of translation in the term of accuracy of translation.This is descriptive qualitative research in the form of embedded research with single-case study design.The data collecting was conducted through content analysis.In this research it can be found that there are 31 expressive illocutionary act in the Big Bad Wolf: The Baddest Day comic and its translation Serigala Jahat: Hari Terburuk. The 61% of the data are considered as accurate translation, and the 31% of the data are considered as less accurate translation. It can be concluded that in translating expressive illocutionary act in a comic, it can not only look at the utterances of the speaker, but also the visualization and the context situation of the picture in the comic.Keywords:speech act, illocutionary, expressive illocutionary act, translating comic, translation accuracy.